The Flower of Evil : On the Phenomenon of Boredom - Zagorac, Ivana (Array, 2014)
This paper focuses on the concept of boredom, which is often described as the product of modern times. However, the writings of Lucretius and Seneca warn of taedium vitae and horror loci, early Christian monks suffered under the demon of acedia, while the malady of melancholy plagued 17th and 18th century Europe. The first part of the paper explores some of the characteristics of boredom, while the second part focuses on an analysis of existential disturbances that can be provoked by boredom. The conclusion deals with the question of whether boredom represents a threat that must be fought against using all means possible, or whether it can be seen as a motivating power to induce far-reaching change.